PENGARUH SISTEM PERPAJAKAN, MACHIAVELLIAN DAN KUALITAS PELAYANAN TERHADAP PENGGELAPAN PAJAK (TAX EVASION) PAJAK HOTEL DAN RESTORAN DI KABUPATEN GIANYAR - Rai Dwi Andayani; Desak Made Candra Nithi (UNHI Press, 2024)
The purpose of this research is to identify the factors that contribute to hotel and restaurant tax evasion in Gianyar Regency, specifically the tax system, Machiavellian strategies, and the quality of service provided. Participants included as many as 66 PHR WPDs who had their information on file with the Gianyar Regency Regional Financial and Asset Management Agency. Saturated sampling was used to select a sample size of 66 participants, and multiple linear regression analysis was used to evaluate them. This study's findings suggest that the tax system significantly and adversely affects tax avoidance. The use of Machiavellian techniques has a notable and beneficial impact on tax avoidance. Tax evasion is significantly and negatively impacted by service quality issues.